Modelling land-use decision-making in encroached forests, Copperbelt Province, Zambia - Akombelwa, Mulemwa (2011)
Natural resource management is an important issue around the world in the light of increased global population size and the subsequent demands arising from an increased need for food, clean water and other ecosystem services. This has often resulted in the encroachment of protected areas and the adoption and maintenance of unsustainable land use practices.